RACIAL DISCRIMINATION AS SEEN IN STOCKETT’S THE HELP - Menggalomo, Nilia R.; Oroh, Elizabeth Z.; Mamentu, Agustine C. (Journal of English Language and Literature Teaching, 2023)
This study aims to reveal about racial discrimination from White race to Black race as seen in Kathryn Stockett’s The Help, by applying qualitative research in which the data are gathered in the form of words and quotation from the novel, internet and other books to substantiate the research. The writers collect the data using two kind of sources, primary and the secondary sources. Primary source is taken from the novel itself and the secondary sources are taken from books internet and other relevant data. In analyzing the data, the writers are using mimetic apporoach which is an imitation, reflection, or representation of Human life. The result of this research shows how the racial discrimination occurs in South America particularly in Jackson, Mississipi. This novel represents how the situation back then in the era of jim crow law, where all of the aspect and accomodation in both black and white are separated for equality but it does not shows the equal treatment for black race. Instead the long preception of black race is inferior and dirty, it costs trauma, poverty, death, for black race. They are still receives all of those bad treats even after all of those suffers and hard-working. Also even when they have to serve the white race and fight for they own freedom. They have to fight against the rules that stand to torture them back then